The case against sugar - Taubes, Gary (New York : Alfred A. Knopf, 2016)
Among Americans, diabetes is more prevalent today than ever; obesity is at epidemic proportions; nearly 10% of children are thought to have nonalcoholic fatty liver disease. And sugar is at the root of these and other critical society-wide, health-related problems. With a combination of science and straight talk, Gary Taubes delves into Americans' history with sugar: its uses as a preservative, as an additive in cigarettes, the contemporary overuse of high-fructose corn syrup. He explains what research has shown about our addiction to sweets. He clarifies the arguments against sugar, corrects misconceptions about the relationship between sugar and weight loss; and provides the perspective necessary to make informed decisions about sugar as individuals and as a society
Introduction: Why diabetes? -- Drug or food? -- The first ten thousand years -- The marriage of tobacco and sugar -- A peculiar evil -- The early (bad) science -- The gift that keeps on giving -- Big sugar -- Defending sugar -- What they didn't know -- The if/then problem: I -- The if/then problem: II -- Epilogue: How little is still too much?
Includes bibliographical references and index
Keywords: Sugar-free diet -- Case studies; Sugar -- Physiological effect -- Popular works; Nutritionally induced diseases -- Popular works; HEALTH & FITNESS / Nutrition; SCIENCE / Chemistry / General; Nutritionally induced diseases; Sugar-free diet; Sugar -- Physiological effect; Sugar-free diet -- Case studies; SCIENCE / Chemistry / General; HEALTH & FITNESS / Nutrition; Case studies; Popular works